Novel oddity detection task differentiates early Alzheimer's disease and major depression. (31st December 2021) - Frei, Marlen; Berres, Manfred; Kivisaari, Sasa L; Monsch, Andreas U.; Kressig, Reto W.; Krumm, Sabine
Abstract: Background: The differentiation between early Alzheimer's disease (AD) and Major depression (MD) is a common clinical challenge. AD‐related neurofibrillary tau‐pathology starts in the perirhinal cortex (PRC) whereas little to no neurodegeneration is found in MD. Thus, testing PRC functioning could help distinguishing these pathologies. The PRC is involved, amongst others, in visual discrimination of complex objects. We assessed the ability of a novel visual oddity detection task to differentiate adults in early stages of AD from those with MD and healthy controls (HCs). Method: Participants had to choose the odd figure out of six highly ambiguous, simultaneously presented Kanji‐like stimuli. The sample included 28 patients in early stages of AD (8 amnestic mild cognitive impairment, 20 Alzheimer's dementia, 14 female, age = 75.74±6.72 years, education = 13.51±3.13 years, MMSE = 26.29±1.94), 26 patients with MD (14 female, age = 61.88±10.82 years, education = 13.31±3.04 years, MMSE = 28.77±1.27), and 25 HCs (11 female, age = 68.98±10.74 years, education = 14.26±3.91 years, MMSE = 29.01±1.04). As proof of concept, only AD patients showed distinct PRC thinning adjusted for age and total intracranial volume (HC vs. AD: t = ‐3.355, p = .001 ; HC vs. MD: t = ‐.596, p = .553). Logistic regressions were performed using demographically adjusted z‐scores of task performance. Result: Incorrect responses predicted group membership of AD vs. MD patients (odds ratio [OR] = 0.45, 95% confidence interval [CI; 0.22, 0.77], p = .011), as well as AD patients vs. HCs (OR = 0.45, 95% CI [0.22, 0.79], p = .012). Furthermore, correct responses predicted group membership of AD patients vs. HCs (OR = 0.35, 95% CI [0.16, 0.66], p = .004), but not between AD patients vs. MD ( p = .11). Omitted responses did not have a distinct effect (AD vs. MD: p =.36; AD vs. HC: p = .051). Conclusion: A novel oddity detection task differentiated patients in early stages of AD from MD patients and HCs. Although further validation is needed, these findings indicate that the task detects early cognitive impairment related to AD and may support differential diagnosis.